Frequency of Burst Abdomen and Associated Risk Factors After Emergency Laparotomy in A Tertiary Care Hospital from Rawalpindi - Abbasi, Muhammad Sheraz; Ashraf, Imran; Noor, Asad; Zaman, Sajid; Shaukat, Abaidullah; Nagra, Bilal Sikandar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the frequency of burst abdomen and associated risk factors after in patients undergoing laparotomy. Study Design: Prospective longitudinal study Place and Duration of Study: Combined Military Hospital Rawalpindi, Pakistan from Jan to Jun 2023 Methodology: One hundred and sixteen patients meeting our inclusion criteria who underwent emergency laparotomy were included in the study. Convenience sampling was performed for patient selection. The primary outcome was development of burst abdomen. Results: Of 116 patients, 75(64.7%) were male and 41(35.5%) were female, with a mean age of 41.11±15.13 years. The major primary diagnosis for which patients underwent laparotomy were peritonitis, intestinal obstruction and blunt trauma. Only 12(10.34%) patients developed burst abdomen. The major risk factors associated with burst abdomen (p< 0.05) were age, history of smoking, anemia, obesity, diabetes mellitus, malnutrition, post-operative ileus, wound infection, wound leakage, post-operative cough and vomiting. Obesity, smoking and vomiting were not significantly associated with development of burst abdomen (p> 0.05). Conclusion: We found that abdominal wound dehiscence, or burst abdomen, occurred in 10.34% patients who underwent emergency laparotomy at our set-up. The associated risk factors included wound infections, anastomotic leaks, and the presence of coexisting conditions like peritonitis, diabetes, anemia, malnutrition and advanced age.